The dilemma of distance: patients with kidney cancer from regional Australia present at a more advanced stage. (March 2014) - Satasivam, Prassannah; O'Neill, Sarah; Sivarajah, Gausihi; Sliwinski, Ania; Kaiser, Celina; Niall, Owen; Goad, Jeremy; Brennan, Janelle
Abstract : Objective: To determine whether patients from regional areas undergoing surgery for kidney cancer present with more advanced disease as a result of geographic isolation. Patients and Methods: Retrospective analysis of 221 patients undergoing surgery for renal cell carcinoma (RCC) from January 2004 to June 2012, from both a metropolitan centre and a large inner regional hospital. Data was collected on age, gender, presentation (incidental or symptomatic), clinical stage and pathological features. The Australian Standard Geographical Classification‐Remoteness Area (ASGC‐RA) is a system developed to allow quantitative comparisons between metropolitan and rural Australia. A score was assigned to each patient based on their location of residence at the time of surgery: metropolitan, RA1; inner regional, RA2; outer regional, RA3. Statistical significance was specified as P < 0.05 on Pearson's chi‐square tests. Results: Patients in each ASGC‐RA group did not differ significantly in age, sex or mode of presentation. Pathological T stage on presentation increased with increasing ASGC‐RA and thus distance from tertiary centres ( P = 0.004). The proportion of patients with ≥T3 disease rose from 30% of RA1 to 73% of RA3 patients ( P = 0.016) treated at our tertiary centre. Similarly, our regional centre had a larger proportion of patients presenting with ≥T3 disease from RA3 (31% vs 5%, P = 0.003). When the 221 patients with RCC were analysed as a group, clinical T stage was significantly associated with ASGC‐RA ( P < 0.001), symptomatic presentation ( P < 0.001), N stage ( P < 0.001), M stage ( P < 0.001) and Fuhrman grade ( P < 0.001). Conclusions: Our data quantifies the detrimental effect of physical distance on the health outcomes of regional Australians with kidney cancer. Australia's unique geography and rural culture may preclude any attempts to centralise cancer care to specialised metropolitan units, as has occurred in other countries.